Modifying geopolymer wettability by plasma treatment and high-carbon fly ash - Růžek, Vojtěch; Louda, Petr; Buczkowska, Katarzyna; Just, Paweł; Prałat, Karol; Ciemnicka, Justyna; Przemysław, Plaskota (Frontiers in Built Environment, 2022)
This paper deals with investigation of changes in geopolymer wettability with increasing mass fraction of high-carbon fly ash and surface treatment by cold atmospheric plasma (CAP) to determine the influence of fly ash on wettability and whether it is a viable method to increase surface wettability for further surface treatment. In this study, multiple samples of geopolymers were prepared, including those with 16% and 32% of high-carbon fly ash from coal-fired power station. Wettability of samples was then measured before and after plasma treatment, both on surface and cut surface by using static sessile drop method to measure the differences in contact angle. While addition of fly ash only had low effect on the wettability, as in most cases, it only lowered the initial contact angle without speeding up the speed of soaking for compact geopolymer and actually slowed the soaking for foamed geopolymer, plasma treatment had significant impact and made the geopolymer completely hydrophobic, making plasma treatment a viable method to increase geopolymer wettability.